Penerapan Metode Waterfall dalam Perancangan Sistem Informasi Administrasi Simpan Pinjam untuk Meningkatkan Efisiensi Layanan BKD Unit Kaligayam - Hanum Dwi Septiani; Wahyu Krishantoro (Fakultas Teknik Universitas Hamzanwadi, 2026)
The Kaligayam Village Credit Agency (BKD) plays a vital role in supporting the rural economy through microfinance services, such as fund deposits and loan disbursement. The design of the Savings and Loan Administration Information System at the Kaligayam Village BKD Unit aims to improve efficiency in financial administration, particularly in recording savings and loan transactions. This system is designed to replace the conventional manual process, which is prone to errors and data duplication. The system was developed using the Waterfall model, a sequential and structured method starting from needs analysis, system design, implementation, and system testing. This type of research includes Research and Development (R&D) with system testing activities through functional testing and user acceptance testing to ensure the system's reliability, accuracy, and usability. The results show that the system is capable of recording member data, savings and loan transactions, and generating financial reports automatically and accurately. The system also provides secure and organized data management features, making it easy for users to access information quickly. The main contribution of this research is the creation of an effective and efficient administrative information system, which can be a reference for system development in other microfinance institutions, as well as supporting faster and more accurate decision-making.